Dinamika Keputusan Keluarga dalam Mengikuti Program Kb pada Keluarga Berpendapatan Umr: Studi Kualitatif dalam Perspektif Hukum Islam: The Dynamics of Family Decision-Making in Family Planning Participation Among Umr-Income Families: A Qualitative Study from an Islamic Law Perspective - Alifa Naura Salsabilla; Ruston Kumaini (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
Indonesia’s relatively high population growth has led to various social and economic challenges, particularly in relation to family welfare. The Family Planning (KB) program serves as a strategic effort to control population growth while improving the quality of family life. This study aims to analyze the dynamics of decision-making among families with income equivalent to the Regional Minimum Wage (UMR) in participating in the Family Planning program from the perspective of Islamic law. The research employs a qualitative method with a case study approach conducted in Candi District, Sidoarjo Regency, involving married couples who are KB participants and whose income corresponds to the UMR. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings indicate that family income conditions constitute an important consideration in the decision-making process regarding the use of family planning, particularly in planning the number and spacing of children to maintain economic balance and quality parenting. In addition to economic considerations, support from husbands and the surrounding social environment also shapes these decisions. From the perspective of Islamic law, family planning based on financial considerations is permissible as long as it is not permanent, does not cause harm, and is agreed upon by both spouses, as it aligns with the objectives of maqāṣid al-sharī‘ah in preserving life, lineage, and wealth.